Brill's Companion to War in the Ancient Iranian Empires - Hyland, John; Rezakhani, Khodadad (Brill's Companions to Classical Studies, 2024)
Brill's Companion to War in the Ancient Iranian Empires examines military structures and methods from the Elamite period through the Achaemenid, Seleucid, Arsacid, and Sasanian empires. War played a critical role in Iranian state formation and dynastic transitions, imperial ideologies and administration, and relations with neighbouring states and peoples from Central Asia to the Mediterranean. Twenty chapters by leading experts offer fresh approaches to the study of ancient Iranian armies, strategy, diplomacy, and battlefield methods, and contextualise famous conflicts with Greek and Roman opponents.